Harder, better, faster, stronger? Retrospective chart review of adverse events of interactions between adaptogens and antidepressant drugs - Siwek, Marcin; Woroń, Jarosław; Wrzosek, Anna; Gupało, Jarosław; Chrobak, Adrian Andrzej (Frontiers in Pharmacology, 2023)
Aim: To systematically evaluate prevalence and clinical characteristics of adverse events associated with the adaptogens and antidepressant drugs interactions in a retrospective chart review.Methodology: 1816 reports of adverse events have been evaluated. Cases were selected for the analysis if pharmacoepidemiological analysis showed the presence of high probability of a causal relationship between adaptogen and antidepressants interaction and the occurrence of adverse event.The following data has been extracted from the reports: age, sex, antidepressant, plant products containing adaptogens, other concomitant medications, clinical consequences of the interactions and their possible mechanism.Results: Adaptogens were involved in 9% of adverse events associated with the concomitant use of antidepressants and other preparations. We have identified 30 reports in which side effects presented causal relationship with the use of antidepressants and adaptogens. Here we present the list of adaptogens with the corresponding antidepressants and the side effects caused by their interaction: Withania somnifera: reboxetine (testicle pain, ejaculatory dysfunctions), sertraline (severe diarrhoea), Sformatowano: Kolor czcionki: Czerwony 2 This is a provisional file, not the final typeset article escitalopram (myalgia, epigastric pain, nausea, vomits, restless legs syndrome, severe cough), paroxetine (generalized myalgia, ophthalmalgia, ocular hypertension). Eleutherococcus senticosus: duloxetine (upper gastrointestinal bleeding), paroxetine (epistaxis), sertraline (vaginal haemorrhage), agomelatine (irritability, agitation, headache, dizziness). Schisandra chinensis: bupropion (arthralgia, thrombocytopenia), amitriptyline (delirium), fluoxetine (dysuria), Tribulus terrestrsis: citalopram (generalized pruritus), escitalopram (galactorrhea), trazodone (psoriasis relapse). Coptis chinensis: mianserine (arrythmias), mirtazapine (oedema of lower limbs, myalgia), fluoxetine (gynecomastia). Cimcifuga racemosa: mianserine (restless legs syndrome), paroxetine (gynecomastia, mastalgia), venlafaxine (hyponatremia). Bacopa monnieri: agomelatine (back pain, hyperhidrosis), moclobemide (myocardial infarction). Gynostema pentaphyllum: duloxetine (back pain). Cordyceps sinensis: sertraline (upper gastrointestinal bleeding), Lepidium meyeni: mianserine (restless legs syndrome). Scutellaria baicalensis: bupropion (seizures).Conclusions: Clinicians should monitor the use of adaptogens by patients undertaking antidepressant drugs. Addition of side effects and pharmacokinetic interactions (inhibition of CYP and pglycoprotein) between those medicines may result in clinically significant adverse events.